(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Antimicrobials, such as antibiotics, are substances used to kill microorganisms or to stop them from growing and multiplying. They are commonly used in human and veterinary medicine to treat a wide variety of infectious diseases. Antimicrobial resistance (AMR) refers to the ability of microorganisms to withstand antimicrobial treatments. The overuse or misuse of antibiotics has been linked to the emergence and spread of microorganisms which are resistant to them, rendering treatment ineffective and posing a serious risk to public health. A well known example of a bacterium that has acquired resistance to multiple antibiotics is Meticillin-resistant Staphylococcus aureus (MRSA).